FREE RADICAL INHIBITORY ACTIVITY AND PHYTOCHEMICAL PROPERTIES ETHANOLIC EXTRACT OF Guazuma ulmifolia LEAVES AND Rheum officinale ROOTS - To'bungan, Nelsiani; Patricius Kianto Atmodjo; Yulistiyanto, Anggoro Chandra (BRIN Publishing (Penerbit BRIN), 2025)
Despite the unique characteristics, the investigation of the antioxidant activity of ethanol extract of Guazuma ulmifolia leaves and Rheum officinale roots extracted by sonication method and associated with phytochemical content, especially rutin compound content has never been conducted. Therefore, this study aimed to evaluate the antioxidant activity and content of phytochemical compounds in ethanol extracts of G. ulmifolia leaves and R. officinale roots. Extraction was conducted through the sonication method using absolute ethanol solvents, followed by qualitative phytochemical testing and rutin quantitative analysis with UV-Vis spectrophotometry. Free radical inhibitor activity (antioxidant activity) was measured through the DPPH method. The results showed that extract of G. ulmifolia leaves contained alkaloids, flavonoids, tannins, and steroids, while R. officinale roots had only flavonoids and tannins. The rutin concentration was higher in G. ulmifolia compared to R. officinale root. However, the antioxidant activity of R. officinale roots (IC50 = 21.14±2.17 μg/mL) was higher than extract of G. ulmifolia leaves (IC50 = 46.05±1.93 μg/mL). The synergistic or antagonistic interaction of phytochemical compounds in the crude extract caused this variation. Consequently, further studies were recommended to identify phytochemical compounds' synergy mechanisms or antagonisms contributing to biological activity.